2016
DOI: 10.4067/s0718-34292016005000019
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic plant extracts from the southwest Amazon for the alternative control of fall armyworms

Abstract: RESUMENEsta investigación tiene el objetivo de hacer una selección de especies vegetales que son propias de la región Amazónica con potencial de uso en el manejo integrado de la oruga militar tardía Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae). Para tal, fue evaluado la eficiencia de extractos hidroalcohólicos de 15 especies vegetales que se son de la región. Los extractos fueron producidos a partir de las hojas, o de la cáscara, o de liana de las plantas. La eficiencia de los extractos (30 mg.m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…AlmeidA et al (2017) analyzed the efficiency of six active ingredients mixed with copaiba oil-resin. SANtOS et al ( , 2016bSANtOS et al ( , 2016c observed the insecticidal potential of pure oils from 11 plant species in the control of the caterpillar, indicating the efficiency of Copaiba (Copaifera sp., Fabaceae), Babassu (Orbignya phalerata Mart., Arecaceae) and Crapwood (Carapa guianensis Aubl., Meliaceae).…”
Section: Corn Pests (Zea Mays L)mentioning
confidence: 99%
“…AlmeidA et al (2017) analyzed the efficiency of six active ingredients mixed with copaiba oil-resin. SANtOS et al ( , 2016bSANtOS et al ( , 2016c observed the insecticidal potential of pure oils from 11 plant species in the control of the caterpillar, indicating the efficiency of Copaiba (Copaifera sp., Fabaceae), Babassu (Orbignya phalerata Mart., Arecaceae) and Crapwood (Carapa guianensis Aubl., Meliaceae).…”
Section: Corn Pests (Zea Mays L)mentioning
confidence: 99%